El Rocío: A socio-symbolic space for (re)production of the Francoist imaginaries - Mancha Castro, José Carlos (Hispania Nova, 2021)
This paper deals with an approach to the popular religious phenomenon of El Rocío during the first years of Francoist regime. The Virgin and her ritual were instrumentalized for the construction and reproduction of Francoist imaginaries in Andalusia. This fact had been tested by national-Catholicism since the Restoration, and it would be intensified to confront the secularist projects and the economic-political reforms of the Spanish Second Republic. From the early stages of the civil war, the ritual was deeply controlled by elements of the national Catholic political culture which served the acceptance of the reactionary and traditionalist values, symbols and ideological model. Also the ritual was used to legitimise processes of nationalization, militarization, fascistization and recatolization. However, there was a hybridization of the collective imaginaries of the two hegemonic political cultures of Francoist regime: the fascist Falangist and the traditionalist national-Catholicism.